Perencanaan Desain Musholla Nurul Ikhlas yang Ergonomis, Efisien dan Responsif terhadap Kebutuhan Masyarakat Parak Mujua Kabupaten Solok - Barkhia Yunas; Yuni Purnama Syafri; Mutia Alius; Dyla Midya Octavia; Wiwin Putri Zayu; Ernawati Ernawati; Rehan Putra Saira; Hendra Febrianto (Pusat Riset dan Inovasi Nasional, 2025)
The Nurul Ikhlas Mosque, also known as Surau Parak Mujua, located in Pakan Akek, Jorong Kajai, Nagari Koto Baru, Solok Regency, is an important center of religious and social activities for the local community. In June 2023, the mosque suffered a major fire that destroyed the entire structure, creating an urgent need to redesign it to be more functional, ergonomic, efficient, and adaptable to local conditions. This community service project aimed to produce an architectural design that not only met structural and functional needs but also accommodated the social aspirations and cultural values of the local community. The methods used in this project included field observations to understand the community's conditions and needs, participatory discussions with local community leaders to explore aspirations and hopes, technical drawings using AutoCAD software, and structural analysis using ETABS to ensure the building's earthquake resistance. Ergonomics were a key consideration in this design, encompassing circulation flow, room dimensions, natural ventilation, and the selection of materials that were friendly and safe for the elderly, children, and people with disabilities. The output of this activity is a variety of design documents, including floor plans, elevations, building sections, floor plans, columns and beams, and 3D visualizations that can be used as a guide for phased construction. This program demonstrates the importance of collaboration between universities and the community in responding to post-disaster infrastructure needs. This knowledge-based, participatory approach is expected to produce a final design that is appropriate to real needs and the local context, and supports better and more sustainable post-disaster recovery.